Isolated Schwannoma of the Olfactory Groove: A Case Report - Nascimento, Luiz Augusto; Settanni, Flávio Aurélio Parente; Filho, José Franscisco de Góis; Sanchez, Isabela Naria Dias; Cavalcante, Bruna Barros; Stávale, João Noberto (International Archives of Otorhinolaryngology, 2015)
Introduction Schwannoma of the olfactory groove is an extremely rare tumor that can share a differential diagnosis with meningioma or neuroblastoma.Objectives The authors present a case of giant schwannoma involving the anterior cranial fossa and ethmoid sinuses.Case Report The patient presented with a 30-month history of left nasal obstruction, anosmia, and sporadic ipsilateral bleeding. Computed tomography of the paranasal sinuses revealed expansive lesion on the left nasal cavity extending to nasopharynx up to ethmoid and sphenoid sinuses bilaterally with intraorbital and parasellar extension to the skull base. Magnetic resonance imaging scan confirmed the expansive tumor without dural penetration. Biopsy revealed no evidence of malignancy and probable neural cell. Bifrontal craniotomy was performed combined with lateral rhinotomy (Weber-Ferguson approach), and the lesion was totally removed. The tumor measured 8.0 × 4.3 × 3.7 cm and microscopically appeared as a schwannoma composed of interwoven bundles of elongated cells (Antoni A regions) mixed with less cellular regions (Antoni B). Immunohistochemical study stained intensively for vimentin and S-100.Conclusion Schwannomas of the olfactory groove are extremely rare, and the findings of origin of this tumor is still uncertain but recent studies point most probably to the meningeal branches of trigeminal nerve or anterior ethmoidal nerves.
Keywords: paranasal sinuses; skull base; neurilemmoma; olfactory nerve; head and neck neoplasms; neoplasms; nerve tissue